Usability Concerns and Design Solutions in Mobile Health Applications for Older Adults - Shuhadah Othman; Nazlena Mohamad Ali; Hyowon Lee; Alan F. Smeaton; Shafrida Sahrani (Journal of ICT Research and Applications, 2026)
Mobile health applications (mHealth) are known for their potential to enhance health delivery and improve health outcomes for older adults. However, despite their broad potential, significant usability concerns persist among older adults, preventing them from gaining advantages from mHealth and hindering their adoption. This paper critically examines the key usability concerns older adults face when interacting with mHealth. This research adhered to the PRISMA guidelines in the process of retrieving and selecting articles, resulting in the review and analysis of 117 articles published between 2014 and 2024. The results highlight several prevalent usability concerns, including complex navigation, overwhelming instructions, inadequate feedback mechanisms, and limited personalization options, which overlook the diverse needs of older users. Furthermore, this study identified design solutions to address these concerns, including straightforward navigation, clear instructions, and consistent layout/design tailored to older adults. Moreover, this paper established a visual representation that maps identified usability challenges to corresponding design solutions, serving as a valuable resource for researchers, designers, and developers working on mobile health applications for older adults. Integrating these solutions into the development process can significantly improve user experience and increase engagement in health interventions.